Bergman vs. Batman. Chwyt technicznej deziluzji w grach wideo na tle praktyk literackich i filmoznawczych - Kubiński, Piotr (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2015)
Bergman vs. Batman. Technical Disillusion as an Artistic Device in Video Games in the Context of Literary and Film Techniques The aim of the article is to present the idea of technical disillusion as an artistic device used in particular videogames. This phenomenon is analyzed using the example of Batman: Arkham Asylum (Rocksteady; 2009). Because of the far-reaching analogies with techniques present in other artistic discourses, the device of technical disillusion is also examined in the context of literature and film – especially in regards to Ingmar Bergman’s Persona. From this perspective, using technical disillusion as a device exposes its artistic potential and enables us to consider games as space for creative exploration.